Automated catalogs available to the public on the direct line, the Arab International University Private Library as a model. (Damascus University Journal of arts and humanities sciences, 2025)
The study aims to introduce the generations of catalogs available on the online line, with an explanation of the advantages of each generation over the previous one, in addition to presenting a list of the most comprehensive criteria necessary to evaluate the sub-system of the catalog available on the direct line. The study sought to evaluate the catalog available on the direct line of the Arab International Private University based on those criteria and the extent to which it is applied. The study followed the case study approach and used the list of criteria as a checklist to collect the necessary data for the research. A set of results were reached, the most important of which is the lack of support in the index for the characteristics of the Arabic language inthe search and the absence of referrals that help it correct the search strategy in the event that it oes not reach the results. The focus was on a set of recommendations to raise the level. Search and retrieval in the studied index to achieve its goal of serving the beneficiaries.
Keywords: (AIU); Automatic index; Direct index; Evaluation